THE EFFECT OF USING ENGLISH MOVIE ON STUDENTS’ ACHIEVEMENT IN WRITING RECOUNT TEXT - Widi Ayu Ningtyas Putri and Rahmad Husein (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2015)
This study was focused on the investigation of the effect of using Science Fictionmovie on students’ achievement in writing recount text. This study discovered theeffect of using English movie on students’ achievement in writing recount text. Itwas conducted by using experimental research design. The population of thisresearch was grade X students of SMA Negeri 1 Stabat divided into two groups,namely experimental and control group. The experimental group was taught byusing English movie, while the control group was taught by using lecturingmethod (without movie). The instruments used to collect the data was writingrecount text. After the data were analyzed, it was found that the value of tobservedwas 4. 367 with the degree of freedom (df)= 68 at the level ofsignificance 0,05. It means that t-observed was higher than t-table (4. 367>1.994). The result of this study showed that teaching recount text by using Englishmovie was higher than that by using lecturing method (without using Englishmovie). It implies that English movie is appropriate to be applied for writingrecount text.